Modification of LaFe1-xCoxO3 oxygen carrier by Silicalite-1 for chemical looping coupled with the reduction of CO2. (September 2022) - He, Xuehui; Wang, Yuhao; Li, Kongzhai; Wang, Hua; Jiang, Lihong; Yuan, Kai; Zheng, Yane
Abstract: A series of LaFe1−x Cox O3 /w%S-1 are used as oxygen carriers in chemical looping reforming of CH4 coupled with the reduction of CO2 process to produce syngas and CO. In this work, the effect of Co doping and Silicalite-1 content on the performance of oxygen carriers can be obtained from reactivity tests. Among LaFe1−x Cox O3 samples, excellent reactivity is achieved over LaFe0.8 Co0.2 O3 and LaFe0.9 Co0.1 O3 . It is found that the introduction of Silicalite-1 can greatly improve the reactivity and stability of the chemical looping process, which can be attributed to that the existence of Silicalite-1 inhibits the agglomeration of the perovskite particles. Among the LaFe1−x Cox O3 /w%S-1 samples with different Silicalite-1 content, LaFe0.9 Co0.1 O3 /10%S-1 and LaFe0.8 Co0.2 O3 /10%S-1 show higher CH4 conversion and CO selectivity in the CH4 oxidation reaction, while only quite smaller amount of carbon deposits formed on the surface of the oxygen carriers. After 20 redox cycles, LaFe0.8 Co0.2 O3 /10%S-1 still shows excellent reactivity and high resistance to carbon deposition. Graphical Abstract: ga1 Highlights: Silicalite-1 could improve the reactivity and stability of oxygen carriers. Silicalite-1 can inhibit the agglomeration of the perovskite particles. LaFe0.8 Co0.2 O3 /10%S-1 exhibits the optimal performance during 20 redox cycles.